Career Lotto: Labor Supply in Winner-Take-All Markets - Wayne A. Grove; Michael Jetter; Kerry L. Papps (Institute of Labor Economics (IZA), 2018)
Are people prone to selecting occupations with highly skewed income distributions despite minuscule chances of success? Assembling a comprehensive pool of potential teenage entrants into professional tennis (a typical winner-take-all market), we construct objective measures of relative ability and earnings projections. We find that prospective tennis professionals are attracted to right-skewed earnings distributions, independent of mean and variance. If skewness in prize money fell to zero, males would be 23% and females 5% less likely to continue pursuing a professional career, on average. Thus, winner-take-all labor markets appear to systematically encourage those with modest talents to pursue long-shot careers.
Keywords: J22; J24; J31; J44; L83; 330; winner-take-all markets; superstar markets; labor supply; human capital; gender differences; skewness preferences